P9a(Cdt-PLA2) from Crotalus durissus terrificus as good immunogen to be employed in the production of crotalic anti-PLA2 IgG - Fusco, Luciano Sebastian (2015)
Four proteins with phospholipase A2 (PLA2) activity, designated P9a(Cdt-PLA2), P9b(Cdt-PLA2), P10a(Cdt-PLA2) and P10b(Cdt-PLA2) were purified from the venom of Crotalus durissus terrificus by two chromatographic steps: a gel filtration and reversed phase HPLC. The profile obtained clearly shows that three of them have a similar abundance. The molecular mass, 14193.8340Da for P9a(Cdt-PLA2), 14134.9102Da for P9b(Cdt-PLA2), 14242.6289Da for P10a(Cdt-PLA2) and 14183.8730Da for P10b(Cdt-PLA2), were initially evaluated by SDS-PAGE and confirmed by ESI-Q-TOF spectrometry, and all of them displayed a monomeric conformation. Also, partial amino acid sequence of each protein was obtained and their alignments with other crotalic PLA2 revealed a high degree of identity among them. Additionally, we studied some pharmacological activities like neurotoxicity, myotoxicity and lethality, which prompted us to pick two of them, P9a(Cdt-PLA2) and P10a(Cdt-PLA2) that resulted to be less toxic that the others, and further characterize them to be used as immunogen. We next injected these last proteins in mice to produce antitoxins against them and ELISA and dot blots reveled that both toxins do not show immunogenic differences, unlike those other pharmacologic activities tested. Furthermore, the antibodies produced cross-reacted with all the isoforms purified demonstrating the feasibility of using only one of them and ensuring the cross-reaction of all.The results obtained show that P9a(Cdt-PLA2) isoform has the lowest toxicity and also a good purification performance; thus this protein may be a promising candidate to be employed in the production of crotalic antitoxins.